Cardiac rehabilitation in COVID-19 pandemic period. (14th October 2021) - Costa, J C; Mouici, I; Bichon-Treulet, L; Nazeyrollas, P; Metz, D
Abstract: Background: The current COVID-19 pandemic constitutes a challenge in cardiovascular disease (CVD) management. Little is known on how the virus impacts cardiac rehabilitation (CR) programs (CRP) safety and efficacy. Aim: To evaluate the efficacy of basic sanitary procedures to limit the risk of virus spreading in patients undergoing cardiac rehabilitation in ambulatory setting. Methods: From august to October 2020, all patients admitted in a single ambulatory CR program were screened for COVID-19 infection before and after CR. Negative naso-pharyngeal swab through RT-PCR was mandatory within seven days before starting the program, and advised after leaving the program. Serologic tests were also advised before and after the CRP. Number of patients were reduced from 9 to 4 in each group, 2 meters distancing respected, and all patients and staff had to wear surgical mask during sessions. Regular hand washing and hydro-alcoholic solutions use were mandatory for both patients and health professionnals. Material disinfection was systematic before and after each session. Results: Among the 81 patients included, 63 (76%) were male, mean age was 57±11 years (see table). Sanitary protection measures were well applied and tolerated, especially use of surgical mask during exercice sessions. After RT-PCR on nasal swab, none (0%) were positive before entering CR and only 2 (2.7%) were tested positive after CR. These two patients were asymptomatic. The other patients in the same group as those having positive nasal test after CR were tested negative and were asymptomatic. According to serological analysis, the same 3 patients (3.8%) had anti-bodies against SARS-COV-2 before and after participating CR (see graph). These 3 patients were negative on nasal swab before and after CR. No seroconversion was observed. Mean delay between first and second RT-PCR on nasal swab and serological analysis were 30±15 and 32±15 days, respectively. In total (before and after CR), 5 patients (6.0%) were tested positive with SARS-COV-2. Those 5 patients were younger (mean age 51 years old versus 58, p=0.2), with better functional capacity before and after CR: respectively 7.1 METs (versus 5.2 METs, p=0.014) and 8.3 METs (versus 6.3 METs, p=0.03). In COVID+ patients, improvement of functional capacity was similar to COVID− patients: respectively 0.8 METs (p=0.9) and 15 Watts (p=0.9). Conclusion: During COVID-19 pandemic, cardiac rehabilitation is not associated with risk of infection with SARS-CoV-2, provided that basic sanitary measures are stricly applied. It is also associated with functionnal capacity improvement, especially in patients who previously had COVID-19. FUNDunding Acknowledgement: Type of funding sources: None.